Costly Concessions: An Empirical Framework for Matching with Imperfectly Transferable Utility - Galichon, Alfred; Kominers, Scott Duke; Weber, Simon (Journal of Political Economy, 2019)
We introduce an empirical framework for models of matching with imperfectly transferable utility and unobserved heterogeneity in tastes. Our framework allows us to characterize matching equilibrium in a flexible way that includes as special cases fully and nontransferable utility models, collective models, and settings with taxes on transfers. We allow for the introduction of a general class of additive unobserved heterogeneity on agents’ preferences. We show existence and uniqueness of an equilibrium under minimal assumptions. We provide two algorithms to compute the equilibrium in our model. We then show that the associated log likelihood has a simple expression and compute its derivatives. An empirical illustration is provided in the appendix.